Lichen on Stone: Aníbal Núñez as World-Ecological Poet. - O'dwyer, Manus (Hispanic Review)
Spanish poet Aníbal Núñez's (1944–1987) commitment to environmental issues has been noted by critics. In this article, however, I historicize Núñez's ecologism, reading him as a "world-ecological" poet whose position in a "semiperipheral" space undergoing rapid modernization allows for insights into the ecological and cultural traumas provoked by capitalist modernity, registering these traumas on both a thematic and a formal level. I will argue that the destabilization of poetic voice that marks his work, his use of irony, collage, and allegory, relate to the disorienting effects of rapid modernization, reflecting a profoundly critical view of the ways in which human and natural resources are set to work in capitalist economies, a perspective that radically decenters the human in ways that are pertinent to what is often termed the "Anthropocene." Spanish poet Aníbal Núñez's (1944–1987) commitment to environmental issues has been noted by critics. In this article, however, I historicize Núñez's ecologism, reading him as a "world-ecological" poet whose position in a "semiperipheral" space undergoing rapid modernization allows for insights into the ecological and cultural traumas provoked by capitalist modernity, registering these traumas on both a thematic and a formal level. I will argue that the destabilization of poetic voice that marks his work, his use of irony, collage, and allegory relate to the disorienting effects of rapid modernization, reflecting a profoundly critical view of the ways in which human and natural resources are set to work in capitalist economies, a perspective that radically decenters the human in ways that are pertinent to what is often termed the "Anthropocene."